Pengaruh Penggunaan Metode Bercerita Terhadap Keaktifan Belajar PAK dan Budi Pekerti Siswa Kelas VIII SMP N 3 Simanindo Tahun Pembelajaran 2024/2025 - Sarah Citra Kasih Silalahi; Tiurma Berasa; Risden Anakampun; Ratna Saragih; Rida Gultom (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine how much positive and significant influence there is between the Use of Storytelling Methods on the Activeness of PAK Learning and Character of Class VIII Students of SMP N 3 Simanindo, with the hypothesis that there is a positive and significant influence between the Use of Storytelling Methods on the Activeness of PAK Learning and Character of Class VIII Students of SMP N 3 Simanindo. This study uses a quantitative descriptive inferential approach, with a population of all students of Class VIII SMP N 3 Simanindo who are Protestant Christians totaling 34 people as the research sample. Data were collected with a closed questionnaire of 38 items compiled by the author based on variable indicators according to expert theory. The questionnaire trial was conducted on 30 student respondents outside the research respondents, and its validity and reliability have been tested. The results of the data analysis show that there is a positive and significant influence between the Use of the Storytelling Method on the Activeness of PAK Learning and Character Education of Class VIII Students of SMP N 3 Simanindo in the 2024/2025 Academic Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.871> rtable (α = 0.05, n = 34) 0.339, thus there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value of 10.035> ttable (α = 0.05, dk = n-2 = 32) 2.03693 thus there is a significant relationship between variable x and variable y. 2) Influence test: a) Regression equation test, obtained regression equation Ŷ = 2.27 + 0.67X. b) Determination coefficient test (r2) = 75.9%. 3) Hypothesis testing using the F test obtained Fcount > Ftable (α = 0.05, dk numerator k = 2, dk denominator = n-23 = 34-2 = 32) namely 98.71 > 3.23, thus Ha is accepted and H0 is rejected.